INFLUENCE OF BRAND IMAGE AND SERVICE QUALITY REGARDING REPURCHASE DECISIONS WITH SHOPPING LIFESTYLE AS A VARIABLE MODERATION IN CONSUMERS OF HILON PRODUCTSIN MEDAN CITY - Aprianta Raskami Sembiring; Paham Ginting; Endang Sulistya Rini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Repeat purchases usually indicate that the product meets consumer approval and consumers are willing to use it again in large quantities. Repurchase Intention is a repurchase activity carried out by consumers of a product with the same brand without being followed by any meaningful feelings towards the product. This research aims to determine and analyze the influence of brand image and service quality on repurchase intention with shopping lifestyle as a moderating variable among consumers of Hilon products in Medan. This research is quantitative research with an associative approach and the nature of the research is a survey. The population in this research is consumers of Hilon products in Medan. The sampling method uses a non-probability sampling method using incidental sampling techniques with a sample size of 165 people. The data is explained with the help of the SPSS For Windows program. The results of the research show that brand image has a positive and significant influence on repurchase intention, service quality has a positive and significant influence on repurchase intention, there is a positive and significant influence of brand image and service quality together on repurchase intention, shopping lifestyle cannot afford moderating the influence of brand image on repurchase intention, shopping lifestyle is not able to moderate the influence of service quality on repurchase intention.